The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/nature21714
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into adiponectin receptors suggest ceramidase activity

Abstract: Adiponectin receptors (ADIPORs) are integral membrane proteins that control glucose and lipid metabolism by mediating, at least in part, a cellular ceramidase activity that catalyses the hydrolysis of ceramide to produce sphingosine and a free fatty acid (FFA). The crystal structures of the two receptor subtypes, ADIPOR1 and ADIPOR2, show a similar overall seven-transmembrane-domain architecture with large unoccupied cavities and a zinc binding site within the seven transmembrane domain. However, the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
220
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(235 citation statements)
references
References 50 publications
14
220
0
1
Order By: Relevance
“…These in vitro and in vivo studies revealed that both AdipoR1 and AdipoR2 exhibit ceramidase activity that is enhanced by adiponectin and reduces cellular ceramide concentration (184, 185). Consistent with these data, crystal structures of both AdipoR1 and AdipoR2 suggest they possess intrinsic ceramidase activity (487). …”
Section: Adiposity and Insulin Resistancementioning
confidence: 56%
“…These in vitro and in vivo studies revealed that both AdipoR1 and AdipoR2 exhibit ceramidase activity that is enhanced by adiponectin and reduces cellular ceramide concentration (184, 185). Consistent with these data, crystal structures of both AdipoR1 and AdipoR2 suggest they possess intrinsic ceramidase activity (487). …”
Section: Adiposity and Insulin Resistancementioning
confidence: 56%
“…These effects of the receptors are strictly dependent on the presence of APN [7]. Furthermore, recent structural insights into the APN receptors point directly at a receptor-inherent ceramidase activity and further highlights the sphingolipid axis as a major primary mediator of APN effects [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…The effects of adiponectin appear to be dependent on receptor-mediated increases in ceramidase activity, resulting in decreased intracellular ceramide concentrations [29]. A very recent study [68] showed that adiponectin receptors themselves possess ceramidase activity.…”
Section: Introductionmentioning
confidence: 98%